Curriculum development : a guide for educators - Boyle, Bill (William F.); Charles, Marie (Los Angeles : SAGE, 2016)
"Curriculum and curriculum issues are at the heart of current debates about schooling, pedagogy and learning. This book will enable practitioners, scholars and academics to understand how to re-design or to suggest changes to curriculum structure, shape and content. Grounded in theory and philosophy, the book also offers practical help in grasping this controversial area."--Page 4 of cover.
Introduction -- 1. Curriculum Evolution -- 2. Developing a National Curriculum: Consultation -- 3. Curriculum Development: Case Specific -- 4. Curriculum Reviewing Criteria: Case Specific -- 5. Science Curriculum: Case Specific -- 6. Early Years Foundation Curriculum: Case Specific -- 7. Balancing Raising Standards with a Well-designed and Broad Curriculum -- 8. Integrating Subjects and Themes -- 9. Curriculum Construction -- 10. Curriculum and Assessment -- 11. Assessment and Testing -- 12. National Curriculum and Summative Testing.
Includes bibliographical references (pages 198-212) and index.
Keywords: Curriculum planning